Trichoderma Asal Akar Kopi Dari Alor: Karakterisasi Morfologi dan Keefektifannya Menghambat Colletotrichum Penyebab Penyakit Antraknosa secara in Vitro - Didiana Yanuarita Molebila; Ade Rosmana; Untung Surapaty Tresnaputra (Jurnal Fitopatologi Indonesia, 2020)
Trichoderma of Coffee Roots From Alor: Morphological characteristic and in vitro Efficacy to Inhibit Colletotrichum Causing Anthracnose Trichoderma is a fungus capable of intimate associations with plant root systems including on coffee plants. This aim of study is to determine the characteristics of Trichoderma morphospecies from coffee roots of Alor origin, East Nusa Tenggara (NTT) and its ability to inhibit the growth of Colletotrichum causing anthracnose disease in-vitro. Root samples of healthy coffee plants were taken from the location of coffee plantations in Alor District, NTT. Isolation of Trichoderma fungi from coffee roots was done by incubating the sterilized coffee roots in a layer of moist filter paper in a Petri dish for seven days. Identification of Trichoderma by observing the characteristics of the colony on the medium of potato dextrose agar (PDA) and microscopic media using microcultures (slide culture). Inhibition of Trichoderma fungi against Colletotrichum was tested by multiple culture methods on PDA media. The results of root incubation in humid conditions showed that there was four morphospecies of Trichoderma fungi, each of which had different characteristic specifications. In vitro antagonism in test on PDA medium, the first three morphospecies against Colletotrichum showed that each Trichoderma could inhibit 70.2%, 65.8%, and 63.3%, respectively, five days after inoculation. This data shows that Trichoderma isolated from coffee roots from Alor has the potential to suppress the growth of anthracnose pathogens.